Land governance and gender The tenure-gender nexus in land management and land policy - Chigbu, Uchendu (CABI, 2021)
This book delivers new conceptual and empirical studies surrounding the design and evaluation of land governance, focusing on land management approaches, land policy issues, advances in pro-poor land tenure and land-based gender concerns. It explores alternative approaches for land management and land tenure through international experiences. Themes include Islamic tenure, reverse migration, matriarchy/matrilineal systems, structural inequality, tenure-responsive planning, land-related instabilities and COVID-19, urban-rural land concerns, women's tenure bargaining, tenure-gender nexus concerns in developing and developed countries.